A week in the woods - Clements, Andrew (New York : Aladdin Paperbacks, 2004)
The fifth grade's annual camping trip in the woods tests Mark's survival skills and his ability to relate to a teacher who seems out to get him.
Booklist
Horn Book
School Library Journal
6.3
5-8
5-8
Keywords: Camping -- Fiction; Survival -- Fiction; Teacher-student relationships -- Fiction